2022
DOI: 10.3390/ijms232113414
|View full text |Cite
|
Sign up to set email alerts
|

MED1 Ablation Promotes Oral Mucosal Wound Healing via JNK Signaling Pathway

Abstract: Mediator complex subunit 1 (MED1) is a coactivator of multiple transcription factors and plays a key role in regulating epidermal homeostasis as well as skin wound healing. It is unknown, however, whether it plays a role in healing oral mucosal wounds. In this study, we investigate MED1’s functional effects on oral mucosal wound healing and its underlying mechanism. The epithelial-specific MED1 null (Med1epi−/−) mice were established using the Cre-loxP system with C57/BL6 background. A 3 mm diameter wound was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…CDK7 could directly phosphorylates Med1 at T1457 to in uence castration-resistant prostate cancer [49]. Med1 has also been shown to regulate the Jun amino-terminal kinase (JNK) /c-Jun pathway [50]. In this study, Med1 was phosphorylated at S1418 after T. gondii infection and dephosphorylated after A-Raf knockout in 3D4/21 cells.…”
Section: Discussionmentioning
confidence: 69%
“…CDK7 could directly phosphorylates Med1 at T1457 to in uence castration-resistant prostate cancer [49]. Med1 has also been shown to regulate the Jun amino-terminal kinase (JNK) /c-Jun pathway [50]. In this study, Med1 was phosphorylated at S1418 after T. gondii infection and dephosphorylated after A-Raf knockout in 3D4/21 cells.…”
Section: Discussionmentioning
confidence: 69%
“… 9 Evidence from recent in vitro wound model studies have shown that c‐Jun expression increases as a result of treatment with different agents, which promotes the migration and proliferation of keratinocytes, thereby accelerating wound healing. 40 , 41 , 42 However, in another study, they showed that high glucose increased the mRNA and protein level of AP1 subunits c‐Fos/c‐Jun, resulting in the activation of AP1 in diabetic skin tissue. 43 In an in vivo wound model, photobiomodulation treatment combined with a topical hydrogel prepared from the fruit of Lycium barbarum was shown to decrease MMP‐1/‐2/‐9 expression as well as c‐Fos/c‐Jun, and increase collagen I/III level, inhibit skin thickening caused by ultraviolet radiation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, phosphorylated AP‐1 is also known to regulate genes involved in wound healing, such as growth factors and MMPs 9 . Evidence from recent in vitro wound model studies have shown that c‐Jun expression increases as a result of treatment with different agents, which promotes the migration and proliferation of keratinocytes, thereby accelerating wound healing 40–42 . However, in another study, they showed that high glucose increased the mRNA and protein level of AP1 subunits c‐Fos/c‐Jun, resulting in the activation of AP1 in diabetic skin tissue 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Cell migration was monitored and photographed after 12, 24, and 36 h, respectively. The relative migration rate was calculated as (original scratch area‐point scratch area)/original scratch area × 100% (Meng et al, 2022).…”
Section: Methodsmentioning
confidence: 99%